Islamic Worldview dan Pendidikan Perempuan - Mujahid, Kasori; Muslimah, Fadhilah Wardatul; Az Zahrah, Fathimah (TSAQOFAH, 2025)
The Islamic worldview is a framework of thought that underpins Muslims' understanding of life and reality, based on the principle of tauhid (monotheism), encompassing both worldly and spiritual dimensions. This article aims to explore the fundamental concepts and key elements of the Islamic worldview and link them to the issue of women's education. The discussion emphasizes how the Islamic worldview supports gender equality in educational opportunities and counters stereotypes that undervalue the need for higher education for women. Through qualitative analysis using a descriptive-analytical approach, the article elaborates on Islamic values that emphasize the importance of education as a means of character development and improving the quality of women's lives. The study reveals that women's education in Islam is not merely a right but also an obligation, playing a strategic role in building a just, inclusive, and sustainable civilization.